La estimulación visual y auditiva para desarrollar el lenguaje en los niños de 2 a 3 años de edad del centro de desarrollo infantil El Paraíso Mágico de la ciudad de Loja periodo septiembre 2013- julio 2014 - Luzón Carrión, Diana Carolina (2015)
The present investigation is a study about "THE VISUAL STIMULATION AND HEARING TO DEVELOP THE LANGUAGE OF CHILDREN FROM 2 TO 3 YEARS OLD IN THE CENTRO DE DESARROLLO INFANTIL EL PARAÍSO MÁGICO IN THE CITY OF LOJA PERIOD, SEPTEMBER 2013-JULY 2014. This thesis make a reference a five objective, the first is based in the theory sustentation about the visual stimulation, auditory and the language of children from 2 to 3 years old, the second refers to diagnose the problem in this case the difficulties that present the children around the acquisition of language in the Cento de DesarrolloInfantil El Paraíso Mágico,the third in designing and adapting one guide of activities visual and auditory to develop the language of children from 2 to 3 years old in the Centro de DesarrolloInfantil el Paraíso Mágico , the fourth focuses on apply this guide of activities and the fifth in validate the results obtained in this guide of activities. To carry out this present investigation, the applied instruments were Melgar test and the test of the “16” and a survey to the teacher of such establishment. "In the child development center, work with a sample 18 children and a teacher. For this investigation we used the following methods; analytical method, hermeneutic-dialectic method, synthetic method, descriptive method, and the applied instruments important results were obtained, the children improved their articulation by 80%, 60% recognized images presented to them and 50% of children improved their discipline or concentration, and the applied survey to the teacher were obtained important data since it was able to demonstrate that a good stimulation is very important in children and from households is necessary for parents to encourage them correctly, so that determined about the visual and auditory stimulation and overall is very suitable in the development physical, cognitive and emotional in children.